Tick lectins: structural and functional properties - Grubhoffer, L; Kovár, V; Rudenko, N (Parasitology, 2004)
Few papers have been published on tick lectins so far, and therefore more data are needed to complete the mosaic of knowledge of their structural and functional properties. Tissue-specific lectin/haemagglutinin activities of both soft and hard ticks have been investigated. Some tick lectins are proteins with binding affinity for sialic acid, various derivatives of hexosamines and different glycoconjugates. Most tick lectin/haemagglutinin activities are blood meal enhanced, and could serve as molecular factors of self/non-self recognition in defence reactions against bacteria or fungi, as well as in pathogen/parasite transmission. Dorin M, the plasma lectin of Ornithodoros moubata, is the first tick lectin purified so far from tick haemolymph, and the first that has been fully characterized. Partial characterization of other tick lectins/haemagglutinins has been performed mainly with respect to their carbohydrate binding specificities and immunochemical features.
Keywords: lektiny; Arthropod Vectors; gastrointestinální trakt; Salivary Glands; hemolymfa; Ticks; Gastrointestinal Tract; klíšťata; Animals; lidé; Hemolymph; členovci - vektory; Lectins; Humans; zvířata; slinné žlázy